The European Union's relations with Latin America and the Caribbean countries in the current geopolitical context - Ioana Elena Secu (European Institute of Romania, 2025)
A study conducted by the European Parliamentary Research Service (2023) notes that the European Union's (EU) relations with Latin America and the Caribbean (LAC) countries are being affected by changes in global power, economic uncertainty, and security threats. The current working paper explores the nature of this relationship, particularly in the period following the start of Russian aggression against Ukraine (2022), as this event has transformed socio-economic and political partnerships around the world. With this in mind, this paper argues that, even under these tense conditions, the strategic partnership between the EU and LAC is constantly evolving at all levels and can be deepened through increasing political dialogue, a rethinking of trade agreements (for example, the last adaptation of the EU-MERCOSUR trade agreement in December 2024), and new EU post-conflict initiatives like "The New Agenda for Relations between the European Union and Latin America and the Caribbean".
Keywords: Y8; 330; Latin America and the Caribbean; European Union; global consequencesof the conflict in Ukraine; EU-LAC trade; EU-LAC strategic partnership; Mercosur